PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN, MANAJEMEN MODAL KERJA & LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN - Dewi, Luh Gede Regina Puspitasari; Abundanti, Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.07.TAHUN.2023DO - 10.24843/EEB.2023.v12.i07.p01, 2023)
Profitability is the company ability to generate profits. Profitability provides a measure of a company's management effectiveness and efficiency. The level of fluctuating profitability is influenced by internal and external factors of the company. Internal factors can be form of financial ratios to determine the strengths and weaknesses of a company. This study aims to explain the effect of liquidity, firm size, working capital management, and leverage on firm profitability. This research was conducted on Sub-Sector Textile Companies listed on the Indonesia Stock Exchange from the  2018-2020 period. The population in this study was 20 sub-sector textile companies and the number of research samples used was 17 companies with the purposive sampling method. Data analysis technique in this study used multiple regression analysis and data collection was carried out by non-participant observation methods. Based on the results of research analysis found that liquidity has a positive effect on firm profitability. Firm size has a positive effect on firm profitability. Working capital management has no significant effect on firm profitability. Leverage has a positive effect on firm profitability.